Microsoft SQL server 2008 analysis services unleashed - Gorbach, Irina (Sams Pub., 2009)
The ultimate guide for anyone who is planning to use the latest version of Analysis services. It gives readers insight into the way Analysis services functions, and explains practical methods for designing and creating multidimensional objects. It also provides valuable insight into the reasons behind the design decisions taken by the product development team.